Challenging the Monomyth: Hera's Female Hero's Journey in The Lord of the Rings: The War of the Rohirrim (PANOPTICON: Journal of English Studies, 2025)
This study conducts a narrative analysis of the character Hera in The Lord of the Rings: The War of the Rohirrim through the theoretical lens of Joseph Campbell's monomyth. Employing a descriptive qualitative method, the research scrutinizes key dialogues and sequences to map Hera's arc onto the hero's journey framework. The findings demonstrate that Hera's trajectory incorporates twelve of the seventeen monomyth phases, successfully fulfilling the three core stages of departure, initiation, and return. However, the analysis reveals that the narrative strategically omits certain archetypal phases, such as the refusal of the call and supernatural aid, to craft a heroism defined by agency, resilience, and strategic intellect rather than passive reluctance or external validation. This study concludes that while Hera's journey validates the structural universality of Campbell's model, it also adapts and reframes it, offering a significant contribution to the discourse on female heroism in contemporary fantasy cinema. The research underscores the monomyth's enduring utility while highlighting its evolution in modern, gender-conscious storytelling.